Association between the volume of fluid resuscitation and mortality modified by disease severity in patients with sepsis in ICU: a retrospective cohort study - Rui Zheng; Ling Lin; Xinhao Jin; Weichao Liao (BMJ Open)
Objective The important effect modifiers of high disease severity on the relationship between the different volumes of early fluid resuscitation and prognosis in septic patients are unknown. Thus, this study was designed to assess whether the efficacy of different volumes in the early fluid resuscitation treatment of sepsis is affected by disease severity.Design Retrospective cohort study.Setting Adult intensive care unit (ICU) patients with sepsis from 2001 to 2012 in the MIMIC-III database.Interventions The intravenous fluid volume within 6 hours after the sepsis diagnosis serves as the primary exposure. The patients were divided into the standard (≥ 30 mL/kg) and restrict (<30 mL/kg) groups. Disease severity was defined by the sequential organ failure assessment (SOFA) score at ICU admission. Propensity score matching analysis was performed to ensure the robustness of our results.Primary and secondary outcome measures The primary endpoint of this study was 28-day mortality. Days without needing mechanical ventilation or vasopressor administration within 28-day of ICU admission serving as the secondary endpoint.Results In total, 5154 consecutive individuals were identified in data analysis, 776 patients had a primary end-point event, 386 (49.68%) in the restrict group and 387 (49.81%) in the standard group. Compared with the restrict group, the standard group had higher 28-day mortality (adjusted HR, 1.32; 95% CI 1.03 to 1.70; p=0.03) in the subgroup with a sequential organ failure assessment (SOFA) score ≥10. By contrast, the risk of mortality reduction was modest in the subgroup with an SOFA score <10 (adjusted HR, 0.85; 95% CI 0.70 to 1.03; p=0.10). The effect of the interaction between the SOFA score and fluid resuscitation strategies on the 28-day mortality was significant (p=0.0035).Conclusions High disease severity modifies the relationship between the volume of fluid resuscitation and mortality in patients with sepsis in the ICU; future studies investigating this interaction are warranted.